Taste or statistics? A correspondence study of ethnic, racial and religious labour market discrimination in Germany - Ruud Koopmans; Susanne Veit; Ruta Yemane (Ethnic and Racial Studies, 2019)
In this study we compare rates of discrimination across German-born applicants from thirty-five ethnic groups in which various racial and religious treatment groups are embedded, this study allows us to better distinguish taste and statistical sources of discrimination, and to assess the relative importance of ethnicity, phenotype and religious affiliation as signals triggering discrimination. The study is based on applications to almost 6,000 job vacancies with male and female applicants in eight occupations across Germany. We test taste discrimination based on cultural value distance between groups against statistical discrimination based on average education levels and find that discrimination is mostly driven by the former. Based on this pattern, ethnic, racial and religious groups whose average values are relatively distant from the German average face the strongest discrimination. By contrast, employers do not treat minority groups with value patterns closer to Germany's different from ethnic German applicants without a migration background.
Keywords: 330; ethnic discrimination; taste-based and statistical discrimination; field experiment; race and religion; value distance; education levels